What to Do Here? What to Do There? The Effect of Change in Organization Size on Public Management. Issue 4 (2nd October 2017) - Krøtel, Sarah M. L.; Villadsen, Anders R.; Hansen, Morten B.
ABSTRACT: For a long time, researchers have been interested in the consequences of creating larger public organizations. The outcomes of changes in the size of public organizations have been relatively widely studied; however, much less is known about the internal processes through which these outcomes are actually achieved. This article explores whether changes in organizational size affect public management. As endogeneity is an inherent problem when studying outcomes of organizational size, we apply a quasi-experimental design in order to establish the causal linkage between size and different elements of public management. We use unique survey data collected before and after a large reform that changed the size of most Danish municipalities. The results suggest that public management related to daily operations is generic and not affected by size, whereas public management related to overall tasks such as creating a vision, servicing the mayor, and maintaining external relations is positively affected by size changes.